Companies' sustainability transitions : Key drivers and challenges - Heikkala, Anna (My University, 2025)
This thesis explores the drivers and challenges of companies’ sustainability transitions, which as a topic is gaining relevance as global environmental and social pressures are growing. Companies can have a significant effect in the surrounding society and environment, which is why understanding the factors that influence their transitions is essential. This thesis identifies key drivers such as shifting societal values, growing consumer awareness, activism, the influence of social media, technological advancements and evolving regulatory frameworks. These forces create both pressure and opportunities for companies to adopt more responsible practices. At the same time, businesses face multifaceted challenges in the transition process. High initial investment costs, complex and inconsistent regulations, bureaucratic obstacles, and resistance to change within organisations can slow down or complicate the process. By examining these factors, the thesis provides insights into how companies can better manage sustainability transitions and what factors affect businesses while they are aiming to achieve long-term, systemic change.

Tämä tutkielma tutkii yritysten vastuullisuussiirtymien ajureita ja haasteita. Aihe on yhä ajankohtaisempi ympäristöongelmien ja yhteiskunnallisten haasteiden kärjistyessä. Yrityksillä on merkittävä rooli ympäröivän yhteiskunnan ja ekosysteemien muokkaajana, minkä takia on tärkeää ymmärtää yritysten omia vastuullisuussiirtymiä. Tutkielma tunnistaa useita keskeisiä ajureita, kuten yhteiskunnallisten arvojen muuttuminen, kasvava tietoisuus kuluttajien keskuudessa, aktivismi, sosiaalisen median vaikutukset, teknologinen kehitys ja muutokset lainsäädännöllisissä viitekehyksissä. Nämä tekijät luovat yrityksille sekä paineita että mahdollisuuksia siirtyä vastuullisempiin toimintatapoihin. Samalla yritykset kohtaavat monia haasteita siirtymäprosessin aikana. Investointien korkeat kustannukset, monimutkainen ja epäyhtenäinen sääntely, byrokraattiset haasteet ja sidosryhmien muutosvastarinta voivat hidastaa tai hankaloittaa prosessia. Tutkimalla näitä ajureita ja haasteita, tämä tutkielma tarjoaa näkökulmia siihen, miten yritykset voivat johtaa vastuullisuussiirtymiä tehokkaammin ja mitkä tekijät vaikuttavat yrityksiin niiden pyrkiessä pitkäaikaiseen, systemaattiseen muutokseen kohti kestävämpää liiketoimintaa.
Keywords: sustainability transition, corporate social responsibility, sustainable development, challenges, drivers, vastuullisuussiirtymä, vastuullinen liiketoiminta, kestävä kehitys, haasteet, ajurit